PANCASILA ON `AUDAT AL-FIRDAUS: AN INTERPRETATION OF INDONESIA'S INDEPENDENCE HISTORY THROUGH ARABIC LITERATURE - Muhammad Kusuma Wardhana (Journal of Arabic Literature (JaLi), 2024)
This research will discuss one of the Arabic literary works that explicitly addresses the documentation of the history of the Indonesian struggle for independence in 1945 — `Audat al-Firdaus, a drama work by Ali Ahmad Bakatsir. This work tells the story of the dynamics that occurred among the leaders of the Nation—Soekarno, Mohammad Hatta, and Sutan Syahrir—in formulating the ideal ideology to legitimize the proclamation event at Ikada Field, which presents a narrative quite different from the historical documentation known to the Indonesian people. In fact, some of the attachments included in this writing are the author's interpretations in appreciating Indonesia's independence. One of the most striking aspects is that the lyrics of Indonesia's national anthem are written in Arabic language. By using two theoretical approaches: Post-Colonial Literature from Homi Bhabha and Hegemony from Antonio Gramsci, the researcher found an interesting discovery that Bakatsir deliberately created Audatul Firdaus to introduce the socialist ideology of Pancasila as a form of pan-Islamic revolution in the Middle East. This research also found that the connection between Arab writers and Indonesia is not merely as a conduit for Islamic Education that originated earlier in the Middle East, but they are also responsible for the dissemination of nationalist and political ideology in Indonesia for Arabic communities to break free from the shackles of Western imperialism.